The psychostimulant drug khat (Catha edulis): A mini-review. (September 2015) - Nichols, Tyler; Khondkar, Proma; Gibbons, Simon
Graphical abstract: Highlights: Khat is a mild psycho-stimulant drug consumed by millions of people globally every day. Its consumption is an integral component of the socioeconomic traditions of several cultures. The primary active constituent is cathinone, which rapidly degrades upon harvest and converts into cathine and nor ephedrine. Khat contains complex alkaloids such as the cathedulins as well as tannins, flavonoids and glycosides. ABSTRACT: Khat ( Catha edulis Forsk) is a shrub native to the Horn of Africa and the Middle East. The leaves of this small tree are chewed by millions worldwide as a mild, amphetamine-like psychostimulant drug. Whilst khat has enjoyed grey-area legality in many countries including the United Kingdom that otherwise prohibit the use of recreational drugs, recent years have seen the appearance of new legislation to control its production, importation and consumption. This mini-review will consolidate what is known about the pharmacology, chemistry, and effects on health of khat to provide a brief synopsis of the properties of this plant stimulant.